Evaluation of the GrovacTM system for decontamination of retail beef trimmings to control E. coli O157:H7 and Salmonella - R. Forgey; T. Herald; L.J. Franken; C.A. Tanus; Randall K. Phebus; James L. Marsden (Kansas Agricultural Experiment Station Research Reports, 2005)
The Grovac™ intervention system was evaluated for its effectiveness in reducing E. coli O157:H7 and Salmonella inoculated on the surfaces of beef trimmings. Designed to be used in a batch process, the Grovac™ system involves treating beef trimmings in a mixture of citric acid and a hypotonic salt solution while tumbling under vacuum. Beef trimmings were inoculated with a five-strain cocktail of E. coli O157:H7 and Salmonella, then subjected to no treatment, water with a 1-hour drain treatment, water with an overnight drain treatment, Grovac™ with a 1-hour drain treatment, and Grovac™ with an overnight drain treatment. Data indicated that the Grovac™ system may be a viable method for retailers to use with in-house beef grinding operations to reduce E. coli O157:H7 and Salmonella risks. Reductions in these pathogen populations were 85 and 80%, respectively, after draining for 18 hours at 36°F.
Keywords: Cattlemen' s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Grovac™; E. coli O157:H7; Salmonella; Retail beef